Samodzielność gminy w zakresie wykonywania zadań z zakresu edukacji publicznej a uprawnienia kuratora oświaty - Śwital, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Celem artykułu jest wykazanie, że jednostki samorządu terytorialnego posiadają kompetencje w zakresie zadań oświatowych. Analiza stanu prawnego skłania do postawienia tezy, że odpowiedzialności za działanie systemu oświaty nie towarzyszy realna samodzielność jednostek samorządu terytorialnego w zakresie wykonywania zadań oświatowych. Wprowadzane regulacje prawne ograniczają samodzielność samorządu w zakresie realizacji jej zadań własnych, które jednostki samorządu terytorialnego wykonywać powinny na własną odpowiedzialność. W aktualnym stanie prawnym dochodzi jednak do ograniczenia samodzielności jednostek samorządu terytorialnego przy wykonywaniu zadań poprzez wydawanie wiążących opinii o charakterze pozytywnym przez kuratora oświaty.

The purpose of the article is to demonstrate that local government units have competence over educational tasks. Analysis of the legal state leads to the thesis that the responsibility for the operation of the educational system is not accompanied by real independence of local government units in the performance of educational tasks. The legal regulations being introduced limit the self-government’s independence in carrying out its own tasks, which local government units should carry out on their own responsibility. However, in the current state of the law, there is a restriction on the independence of local government units in carrying out tasks through the issuance of binding opinions of a positive nature by the superintendent of education.
Independence of the municipality in the performance of public education tasks vs. the powers of the superintendent of education
Keywords: samodzielność; oświata; edukacja publiczna; kurator oświaty; opinia; independence; education; public education; superintendent of education; opinion